2015
DOI: 10.1155/2015/593747
|View full text |Cite
|
Sign up to set email alerts
|

Hip Arthroplasty in a Patient with Transfemoral Amputation: A New Tip

Abstract: Femoral fractures in amputation stump are challenging injuries to manage. The authors describe a case of a 51-year-old patient with a right above knee amputation, who had a right hip femoral neck fracture. In this technical note, we describe a technical and surgical procedure with intraoperative tips and tricks, in which we use commonly available materials, for the safe management in such clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 6 publications
0
16
0
5
Order By: Relevance
“…Este tipo de cuadro causa una alta tasa de morbilidad y mortalidad en el mundo; sin embargo, la artroplastia ha cambiado el pronóstico de la fractura medial de cadera. 1,2 La fractura de cuello femoral en un miembro con amputación supracondílea no es una lesión común de encontrar y hay pocas publicaciones al respecto. 1 Se estima que representa el 0,067% de todas las artroplastias de cadera.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Este tipo de cuadro causa una alta tasa de morbilidad y mortalidad en el mundo; sin embargo, la artroplastia ha cambiado el pronóstico de la fractura medial de cadera. 1,2 La fractura de cuello femoral en un miembro con amputación supracondílea no es una lesión común de encontrar y hay pocas publicaciones al respecto. 1 Se estima que representa el 0,067% de todas las artroplastias de cadera.…”
Section: Discussionunclassified
“…1,2 La fractura de cuello femoral en un miembro con amputación supracondílea no es una lesión común de encontrar y hay pocas publicaciones al respecto. 1 Se estima que representa el 0,067% de todas las artroplastias de cadera. 4 Se sabe que la amputación de un miembro provoca cambios osteoarticulares y musculares en el miembro afectado, así como también en el contralateral: 2,3 • aumento de la osteoartritis tibiofemoral y femororrotuliana del lado no amputado.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Some authors have reported tricks to obtain fracture reduction in amputees using skeletal or skin traction applied to a fracture table to restore femoral length. [ 1 2 3 4 5 6 ]…”
Section: Discussionmentioning
confidence: 99%